2017
DOI: 10.1016/j.tcs.2016.07.022
|View full text |Cite
|
Sign up to set email alerts
|

On a class of languages with holonomic generating functions

Abstract: We define a class of languages (RCM) obtained by considering Regular languages, linear Constraints on the number of occurrences of symbols and Morphisms. The class RCM presents some interesting closure properties, and contains languages with holonomic generating functions. As a matter of fact, RCM is related to one-way 1-reversal bounded k-counter machines and also to Parikh automata on letters. Indeed, RCM is contained in L-NFCM but not in L-DFCM, and strictly includes L-CPA. We conjecture that L-DFCM subset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Finally, we will show an interesting language that is both context-free and strongly counting-regular. This language was presented in [31] as a member of the class RCM -a class defined as follows: RCM is the class of the languages given by < R, C, µ > where R is a regular language, C a system of linear constraints and µ, a length-preserving morphism that is injective on R ∩ [C]. The specific language we denote by L RCM is defined as follows:…”
Section: Verifies That For Eachmentioning
confidence: 99%
“…Finally, we will show an interesting language that is both context-free and strongly counting-regular. This language was presented in [31] as a member of the class RCM -a class defined as follows: RCM is the class of the languages given by < R, C, µ > where R is a regular language, C a system of linear constraints and µ, a length-preserving morphism that is injective on R ∩ [C]. The specific language we denote by L RCM is defined as follows:…”
Section: Verifies That For Eachmentioning
confidence: 99%
“…Despite their expressiveness, Parikh automata retain some decidability: nonemptiness, in particular, is NP-complete [12]. For weakly unambiguous Parikh automata, inclusion [7] and regular separability [8] are decidable as well. Figueira and Libkin [12] also argued that this model is well-suited for querying graph databases, while mitigating some of the complexity issues related with more expressive query languages.…”
Section: Introductionmentioning
confidence: 99%
“…In [11], it was shown that there is a polynomial time algorithm to decide, for fixed k, l whether the shuffle of two NCM(k, l) machines is contained in a DCM(k, l) machine. In addition, DCM was studied in [12] as part of an interesting conjecture involving holonomic functions. The authors define a family RCM that is obtained from the regular languages via so-called linear constraints on the number of occurrences of symbols, and homomorphisms.…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that all RCM languages have generating functions which are all holonomic functions. The class of holonomic functions in one variable is an extension of the algebraic functions which contains all those functions satisfying a linear differential equation with polynomial coefficients [12]. They conjectured that DCM is contained in RCM, implying that all DCM languages have holonomic generating functions.…”
Section: Introductionmentioning
confidence: 99%